1986
DOI: 10.1111/j.1365-2125.1986.tb02838.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient bradycardia and subsequent sinus tachycardia produced by intravenous adenosine in healthy adult subjects.

Abstract: Adenosine was administered in increasing intravenous bolus doses to nine healthy volunteers. A transient decrease in heart rate was observed which occurred about 20 s after injection. This was due to a reduction in sinus rate and/or transient block of conduction through the atrioventricular node, and lasted less than 10 s. An increase in sinus rate which followed any transient bradycardia was also observed. The maximum bradycardia and maximum tachycardia were each significantly related to the logarithm of aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…However, some cardioexcitatory effects such as positive chronotropic effects as well as positive inotropic effects have been described (Burnstock & Meghji, 1983;Watt & Routledge, 1986). Recently it has been shown that both adenosine (La Orden et al, 1986) and its stable analogue, NECA (Hernandez et al, 1989), increased cardiac automaticity in the isolated right ventricle of the rat.…”
Section: Discussionmentioning
confidence: 99%
“…However, some cardioexcitatory effects such as positive chronotropic effects as well as positive inotropic effects have been described (Burnstock & Meghji, 1983;Watt & Routledge, 1986). Recently it has been shown that both adenosine (La Orden et al, 1986) and its stable analogue, NECA (Hernandez et al, 1989), increased cardiac automaticity in the isolated right ventricle of the rat.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accord with previous reports of negligible effects of adenosine on inotropic state in either direction (Buckley et al, 1961;Lammerant & Becsei, 1973;Urthaler et al, 1981;Burnstock & Meghji, 1983 (3.5 mg). This dose has been reported to cause minimal cardiac electrophysiological effects (Watt & Routledge, 1986b), suggesting a difference in the dose response with respect to these two effects of adenosine.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular end diastolic pressure (LVEDP) and indices of contractility (peak LV dP/dt and peak LV dP/dt/P) were recorded using a Millar micromanometer-tipped catheter positioned in the left ventricle. Hearts were paced at 100 beats min-1, using a bipolar pacing electrode in the right ventricle, to prevent adenosineinduced alterations in heart rate (Watt & Routledge, 1986b).…”
Section: Methodsmentioning
confidence: 99%
“…Adenosine is an endogenous nucleoside with varied pharmacological actions (Lancet, 1985), which in man include dose-related respiratory stimulation (Watt & Routledge, 1985) and biphasic changes in heart rate (Watt & Routledge, 1986). There is some evidence of possible increases in adenosine sensitivity with increasing age.…”
Section: Introduction Methodsmentioning
confidence: 99%